MENJAGA KESEHATAN MENTAL DENGAN PENDEKATAN SHALAT: ANALISIS SANAD DAN MATAN HADIS - Pasiska, Nurlaila Kamsi, Rama Wijaya Kesuma Wardhani (INSTITUT AGAMA ISLAM NEGERI METRO, 2019)
Abstract This paper seeks to open insight into the study of psychology that is in the Sunnah, regarding mental health. As one source of teachings in Islam, the Hadith contains information and knowledge, including mental health problems in the world of psychology today. With the approach of the study of sanad and matan hadith, the writer tries to explore texts that discuss the topic of mental health and its relevance in the hadith. then it can be concluded that 1) maintaining mental health in the perspective of the Sunnah based on the idea of ​​moderation in meeting the needs of life with a spirituality approach and, 2) the method of spiritual Hadith realizing mental health, among others by praying as a solution to mental illness. Achievements by the method of prayer can be seen from the lives of prophets and friends, with themselves, relationships with others, and the universe that all come together in harmony.